A phase I trial of metformin in combination with vincristine, irinotecan, and temozolomide in children with relapsed or refractory solid and central nervous system tumors: A report from the national pediatric cancer foundation. (23rd September 2022) - Metts, Jonathan L.; Trucco, Matteo; Weiser, Daniel A.; Thompson, Patrick; Sandler, Eric; Smith, Tiffany; Crimella, Jessica; Sansil, Samer; Thapa, Ram; Fridley, Brooke L.; Llosa, Nicholas; Badgett, Thomas; et al.
Abstract: Background: Patients with relapsed and refractory solid and central nervous system (CNS) tumors have poor outcomes and need novel therapeutic options. Vincristine, irinotecan, and temozolomide (VIT) is a common chemotherapy regimen in relapsed pediatric tumors with an established toxicity profile. Metformin shows preclinical anti‐cancer activity through multiple pathways. Methods: The objective of this Phase I trial was to establish the maximum tolerated dose (MTD) and recommended Phase II dose (RP2D) of metformin in combination with VIT in children with relapsed and refractory solid and CNS tumors. A 3 + 3 design was used to test the addition of metformin at five dose levels (666, 999, 1333, 1666, and 2000 mg/m 2 /day). Therapy toxicity, pharmacokinetics, and radiologic response to treatment were evaluated. Results: Twenty‐six patients (median age 13 years, range 2–18 years) were enrolled with 22 evaluable for toxicity. The most common diagnoses were Ewing sarcoma ( n  = 8), rhabdomyosarcoma ( n  = 3) and atypical teratoid/rhabdoid tumor ( n  = 3). The MTD was exceeded at Dose Level 5 due to two dose‐limiting toxicities; both were Grade 3 diarrhea requiring prolonged hospitalization and intravenous fluids. The MTD was not determined due to study closure with less than six patients enrolled at Dose Level 4. Frequently observed toxicities were gastrointestinal (most notably diarrhea) and hematologic. Amongst 16 patients evaluable for best overall response, there was one complete response (Ewing sarcoma), three partial responses (Ewing sarcoma, glioblastoma multiforme, and alveolar rhabdomyosarcoma), and five patients with stable disease. Conclusions: The MTD of VIT with metformin was not determined due to premature study closure. We recommend an RP2D of Dose Level 4, 1666 mg/m 2 /day. Radiographic responses were seen in multiple tumor types. Further evaluation for efficacy could be investigated in a Phase II trial.